Budget of the Locality of Engativá, distributed resources to satisfy your needs (2018)
This essay is the result of the analysis made to the methodological process used to distribute the budget in Engativá, initially through the process of how the district of Bogotá distributes the resources to the 20 localities that comprise it. The reasons for writing on this subject are related to knowing and analyzing the execution of the investment made by Engativá with the resources that are assigned to meet their needs. As part of the development of this paper, they are shown in the Engativá local development plan for the 2017-2020 period, which will be analyzed to know how efficient the methodological process currently used is for the distribution of budget resources. Assigned by the District of Bogotá to the Engativá Local Development Fund.